Low bone mineral density is found in low weight female youth with avoidant/restrictive food intake disorder and associated with higher PYY levels - Aluma Chovel Sella; Kendra R. Becker; Meghan Slattery; Kristine Hauser; Elisa Asanza; Casey Stern; Megan Kuhnle; Nadia Micali; Kamryn T. Eddy; Madhusmita Misra; Jennifer J. Thomas; Elizabeth A. Lawson (Journal of Eating Disorders, 2023)
Abstract Background Avoidant/restrictive food intake disorder (ARFID) is a restrictive eating disorder commonly associated with medical complications of undernutrition and low weight. In adolescence, a critical time for bone accrual, the impact of ARFID on bone health is uncertain. We aimed to study bone health in low-weight females with ARFID, as well as the association between peptide YY (PYY), an anorexigenic hormone with a role in regulation of bone metabolism, and bone mineral density (BMD) in these individuals. We hypothesized that BMD would be lower in low-weight females with ARFID than healthy controls (HC), and that PYY levels would be negatively associated with BMD. Methods We performed a cross-sectional study in 14 adolescent low-weight females with ARFID and 20 HC 10–23 years old. We assessed BMD (total body, total body less head and lumbar spine) using dual x-ray absorptiometry (DXA) and assessed fasting total PYY concentration in blood. Results Total body BMD Z-scores were significantly lower in ARFID than in HC (− 1.41 ± 0.28 vs. − 0.50 ± 0.25, p = 0.021). Mean PYY levels trended higher in ARFID vs. HC (98.18 ± 13.55 pg/ml vs. 71.40 ± 5.61 pg/ml, p = 0.055). In multivariate analysis within the ARFID group, PYY was negatively associated with lumbar BMD adjusted for age (β = -0.481, p = 0.032). Conclusion Our findings suggest that female adolescents with low-weight ARFID may have lower BMD than healthy controls and that higher PYY levels may be associated with lower BMD at some, but not all, sites in ARFID. Further research with larger samples will be important to investigate whether high PYY drives bone loss in ARFID.